Comparison of speed and accuracy between manual and computer-aided measurements of dental arch and jaw arch lengths in study model casts - Wibisono, Dinah; Thahar, Bergman; Hambali, Tono S.; Salim, Jono (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2007)
This research is aimed at observing whether there are differences in the measurement results between dental arch length and arch length measured manually and by using computer software, i.e. Corel Draw 12, in study model cast as well as the measurement speed in both techniques. The method used in this research is the descriptive comparative method. The measurement is performed to 52 study model cast samples with the Spee Curve depth of < 1.5 mm, between 1.5 and 3 mm, > 3 mm. The measurements are performed using 2 techniques: a manual technique using a calliper and by using Corel Draw 12, a computer program with a computer scanner. The t-test statistic is used to reveal whether there are differences in the measurement results between the two techniques and which method needs shorter time. Statistically, there are significant differences either in the speed of the measurement or the results of the measurement using both techniques where t-calculated > t table. The deeper the Spee curve, the more different the results from the manual technique and computed technique. The differences are in the range of 0.32 to 0.52 mm for dental arch length and 0.33 to 0.43 mm for arch length. These differences are still acceptable clinically. By referring to the results of this research, it is expected that computer usage can be increased and become an alternative against manual technique of measurement.